Alternative solvents for green chemistry - Kerton, Francesca M. (RSC Publishing, 2009)
Everyone is becoming more environmentally conscious and therefore, chemical processes are being developed with their environmental burden in mind. This also means that more traditional chemical methods are being replaced with new innovations and this includes new solvents. Solvents are everywhere, but how necessary are they? They are used in most areas including synthetic chemistry, analytical chemistry, pharmaceutical production and processing, the food and flavour industry and the materials and coatings sectors. However, the principles of green chemistry guide us to use less of them, or to u.
Keywords: Solvents.; Solvents -- Environmental aspects.; elektronické knihy; electronic books